2020
DOI: 10.1002/adfm.202006970
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Prussian Blue Analogues in Energy Storage and Conversion Applications

Abstract: In recent years, Prussian blue analogue (PBA) materials have been widely explored and investigated in energy storage/conversion fields. Herein, the structure/property correlations of PBA materials as host frameworks for various charge‐carrier ions (e.g., Na+, K+, Zn2+, Mg2+, Ca2+, and Al3+) is reviewed, and the optimization strategies to achieve advanced performance of PBA electrodes are highlighted. Prospects for further applications of PBA materials in proton, ammonium‐ion, and multivalent‐ion batteries are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
209
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(227 citation statements)
references
References 123 publications
(162 reference statements)
3
209
0
2
Order By: Relevance
“…They have also been proposed as insertion cathodes for next-generation batteries, especially SIBs. [27][28][29][30][31] PBAs can be described using the chemical formula…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have also been proposed as insertion cathodes for next-generation batteries, especially SIBs. [27][28][29][30][31] PBAs can be described using the chemical formula…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the M position in this system can be substituted by other redox-active transition metals, such as Mn, Ni, Cu, Co, V, and Cr, thus allowing modification of the electrochemical behavior. [27][28][29][30][31] In this study, the high-entropy approach is applied to the Prussian blue (PB) structure, utilizing metal cations previously reported in conventional single-or dual-metal PBAs. The HE-PBA material Na x (FeMnNiCuCo)[Fe(CN) 6 ], where the different transition metals have been introduced to the M site in equimolarity, is presented.…”
Section: Introductionmentioning
confidence: 99%
“…PBAs are regarded as one of most promising hosts for metal ion intercalation due to high capacity stemming from multi-electron reaction and its 3D open framework with large ionic channels for rapid ion conduction. [153][154][155] Generally, it can be described as…”
Section: Prussian Blue Analogsmentioning
confidence: 99%
“…Due to their open framework of PBAs with enough space for Na + ion accommodation and the advantage of SIBs, the research interest of PBAs as electrode materials in SIBs has been particularly increasing. [ 52 ] KM II Fe III (CN) 6 (M = Mn, Fe, Co, Ni, and Zn) compounds were first examined by Goodenough and co‐workers as cathodes for nonaqueous SIBs. [ 53 ] A reversible capacity less than 70 mAh g −1 was delivered in KM II Fe III (CN) 6 (M = Mn, Co, Ni, and Zn) electrodes originating from the Fe 3+ /Fe 2+ redox couple with single ≈3.0 V plateau.…”
Section: Applications Of Nano‐pbas Themselves For Energy Storagementioning
confidence: 99%